Aptamer-Based Biosensor for Detection of Mycotoxins - Guo, Xiaodong; Wen, Fang; Zheng, Nan; Saive, Matthew; Fauconnier, Marie-Laure; Wang, Jiaqi (Frontiers in Chemistry, 2020)
Mycotoxins are a large types of secondary metabolites appeared by fungi, they pose a great hazard and toxic reactions to human and animals. A majority of countries and regulators, such as European Union, have established series of requirements and set the maximum tolerated levels. The development of high sensitive and specific analytical platform for mycotoxins is much in demand to address new challenges for food safety in worldwide. Due to the superiority of simple, rapid, and low-cost characteristics, aptamer-based biosensors are successfully developed for the detection of various mycotoxins with high sensitivity and selectivity compared with traditional instrumental methods and immunological approaches. In this article, we discuss and analyze the development of aptasensors for mycotoxins determination in food and agricultural products during the last eleven years and cover the literatures from the first report in 2008 until today. In addition, challenges and future trends for the selection of aptamers towards various mycotoxins and aptasensors for multi-mycotoxins analysis are summarized. Given the promising development and potential application of aptasensors, the future researches will witness the great practicability of aptamer-based biosensor for food safety field.